Minimum Wage, Trade and Unemployment in General Equilibrium - Sugata Marjit; Shrimoyee Ganguly; Rajat Acharyya (Center for Economic Studies and ifo Institute (CESifo), 2020)
The path breaking work of Card and Krueger (1993), showing higher minimum wage can increase employment turned the age-old conventional wisdom on its head. This paper demonstrates that this apparently paradoxical result is perfectly plausible in a competitive general equilibrium production structure of a small open economy with a non-traded good, without taking any recourse to monopsony, spatial heterogeneity, heterogeneity of consumers etc. the usual theoretical drivers behind the result. Following Jones and Marjit (1992) we build up a simple general equilibrium model with complementary relationship in production and we show that higher minimum wage can raise aggregate employment. Expansion in the non-traded sector following a wage hike may be consistent with the overall expansion of the export sector in a multi good framework, an unlikely outcome in a conventional two good models which cannot accommodate complementary relationship in production.
Keywords: J20; J30; F11; F16; 330; minimum wage; employment; non-traded good